ENHANCING PUBLIC PASSENGER TRANSPORT ROUTE SELECTION METHODS. A COMPREHENSIVE REVIEW AND FUTURE DIRECTIONS - Gaypov , Sharipbay Jubatovich (Educational Research in Universal Sciences, 2023)
Efficient public passenger transport systems play a pivotal role in addressing urban mobility challenges. The selection of optimal transport routes is a critical aspect of ensuring the effectiveness of these systems. This scientific article reviews current methods for selecting public passenger transport routes and explores avenues for improvement. By analyzing existing methodologies, identifying challenges, and proposing innovative solutions, this article aims to contribute to the advancement of public transportation planning.